TRANSFORMASI DIGITAL WAJAH PERADILAN: PERAN ARTIFICIAL INTELLIGENCE DALAM PENGUATAN INTEGRITAS - Hardhika, Romi (Ikatan Hakim Indonesia (IKAHI), 2023)
In the era of the fourth industrial revolution, human roles have started to be replaced by artificial intelligence (AI) technology. Artificial intelligence is a computational program created to simulate human thinking and decision-making abilities. In the field of justice, several countries have applied AI technology to determine judges handling cases, create transcripts of court proceedings, and even provide legal considerations and sentencing recommendations. Despite having various benefits, the use of AI in the judicial system is not without risks such as security and privacy concerns. Additionally, there are also issues related to the principle of fair trial proceedings. Therefore, there are several conditions that the Supreme Court needs to consider when implementing AI in the Indonesian judicial system. Firstly, the use of AI must be adjusted to the national legal context in Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Electronic Information and Transactions. Secondly, the Supreme Court needs to pay attention to the five principles outlined in the European Ethical Charter on the Use of Artificial Intelligence in Judicial Systems and their environment. Thirdly, decision-making by AI still requires human intervention (hybrid decision-making) to mitigate errors in the system. It is hoped that the integration of AI into the Indonesian judicial system will be able to realize the vision of